ANALISIS GAYA BELAJAR SISWA MATA PELAJARAN EKONOMI (STUDI KELAS XI IPS SMAN 1 PONTIANAK) - Ananda, Rezka Yulianty; Genjik S, Bambang; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to know students learning styles on economic lesson of class XI IPS in SMA Negeri 1 Pontianak. This research is used a case study method with qualitative research type. The data source of this study is students of class XI IPS by selecting students with the highest average economic value in their class. Four students are obtained as data sources. The collection of data is carried out through observation and interviews. Data analysis using data analysis of techniques Miles and Huberman. Data were analyzed using the collection, reduction, to display, and draw conclusions. The results showed that students’ visual learning styles are categorized as good. Students’ auditory learning style has various category; one student in excellent category, two students in moderate category, and one student in less category. Students’ kinesthetic learning style also has various category; three students in moderate category, and one student in less category. It’s mean that each students has learning style with different categories.Keywords: Learning Style, Visual, Auditory, Kinesthetic